2015
DOI: 10.1038/bmt.2015.297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-dose TBI on outcomes of reduced intensity conditioning allogeneic hematopoietic stem cell transplantation for AML

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative therapy for patients with advanced hematologic malignancy, including those with AML. 1 However, allo-HSCT after conventional myeloablative conditioning (MAC) may be associated with a high rate of transplant-related complications. Reduced intensity conditioning (RIC) was developed with the purpose of reducing regimen-related toxicity. 2,3 RIC is increasingly used for allo-HSCT for AML patients who are otherwise considered unfit for MAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…In addition, the benefit of low-dose TBI on neutrophil engraftment was not observed in patients at high risk for graft rejection such as those with two or more HLA mismatches in the HVG direction and those with highrisk disease. Similar results have been previously reported in HLA-matched related RICT [7] and HLA-matched unrelated/ HLA-mismatched RICT [4]. These results suggest that HLAmismatched RICT excluding cord blood transplantation did not always require low-dose TBI to prevent rejection in current clinical practice.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the benefit of low-dose TBI on neutrophil engraftment was not observed in patients at high risk for graft rejection such as those with two or more HLA mismatches in the HVG direction and those with highrisk disease. Similar results have been previously reported in HLA-matched related RICT [7] and HLA-matched unrelated/ HLA-mismatched RICT [4]. These results suggest that HLAmismatched RICT excluding cord blood transplantation did not always require low-dose TBI to prevent rejection in current clinical practice.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that incorporation of low-dose TBI to conditioning regimens reduced the incidence of graft failure in cord blood transplantation [4,5] and SCT in patients with aplastic anemia [6]. Conversely, the addition of low-dose TBI to RIC did not improve neutrophil and platelet engraftment in HLA-matched related SCT [7]. Additionally, administration of low-dose TBI in addition to RIC was not associated with prompt neutrophil engraftment after HLAmatched unrelated or HLA-mismatched unrelated bone marrow transplantation (BMT) [4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This has resulted in similar OS between these approaches [5,10]. Similar to our analysis, a retrospective report from the Japan Society for Hematopoietic Cell Transplantation also observed no difference in survival or NRM when comparing lowdose TBI (≤400 cGy) and fludarabine with non-TBI approaches, including busulfan-and melphalan-based regimens [23]. A retrospective comparison of RIC versus myeloablative conditioning from French investigators reported significantly lower NRM for RIC but similar adjusted relapse rate and OS [24].…”
Section: Discussionsupporting
confidence: 84%
“…Although reduced-intensity stem cell transplantation (RIST) is thought to induce GVL effects via the use of immunosuppressive drugs, a shortened schedule of TBI is sometimes added to the conditioning regimen in clinical practice. A retrospective analysis of the database of the Japan Society for Hematopoietic Cell Transplantation [1] indicated that adjunctive TBI–RIST did not improve outcomes. Conversely, other reports concluded that TBI–RIST led to significantly better outcomes [2, 3].…”
Section: Introductionmentioning
confidence: 99%